Ectopic pregnancy, symptoms, types and health risks: A narrative review (Research, Society and Development, 2023)
Ectopic pregnancy (E.G.) is characterized by the implantation and development of the egg outside the uterine cavity. The most frequent location is the tubal, although it can occur in the ovary, cervix, abdominal cavity or cervix, and can cause major complications. Initial signs and symptoms are characterized by severe pelvic pain and vaginal bleeding, which may lead to hemorrhagic shock and tubal rupture. Exams such as serum dosage at reception (ß-hCG) and transvaginal ultrasound (TVUS) or endovaginal ultrasound depending on gestational age are forms of early diagnosis, which are also part of women's health protocols in Brazil. The objective of this research was to develop a bibliographic review of the literature on ectopic pregnancy (EG) to disseminate theoretical knowledge on this topic; understand ectopic pregnancy (EG) and risk conditions and the diagnosis and clinical picture. The methodology is a qualitative bibliographic research. Ectopic pregnancy (E.G) is still a challenge for public health and accounts for a portion of deaths related to the gestational period.